A novel method for conjugating the terminal amine of peptide ligands to cholesterol: synthesis iRGD-cholesterol. (7th December 2018) - Fete, Matthew G; Betker, Jamie L; Shoemaker, Richard K; Anchordoquy, Thomas J
Aim: Conventional conjugation reactions often involve the use of activated PEG as a linker, but concerns about PEG-mediated reduction in intracellular delivery and enhanced immunogenicity have generated interest in developing methods that eliminate the need for a PEG linker.Materials & methods: Reaction conditions were identified that specifically couples the terminal amine of a cyclic iRGD peptide (CRGDRGPDC) to the hydroxyl moiety of cholesterol through a short carbamate linker.Results & conclusion: Using this method for synthesizing iRGD-cholesterol, peptide ligands can be incorporated into lipid-based delivery systems, thereby eliminating concerns about adverse reactions to PEG. Toxicity and stability data indicate low toxicity and adequate serum stability at low ligand levels.